Morphometric relationships of length-weight and length-length in snow trout Schizopyge niger (Heckel, 1838) from Dal Lake, Kashmir - Hussain, Shafat; Bhat, Farooz Ahmad; Maqsood, Hakim Mudasir; Balkhi, Masood ul Hassan; Najar, Ali Mohd (Indian Journal of Fisheries, 2018)
The present study elucidates the length-weight (LWR) and length-length (LLRs) relationships in Alghad snowtrout Schizopyge niger (Heckel, 1938), an economically and commercially important fish species of Kashmir. In total, 238 S. niger samples ranging in total length from 62-367 mm and 10-491 g in body weight were studied over a period of one year (November 2015 to October 2016). The results showed that the allometric coefficient ‘b’ in males (2.8391) was close to isometric value (≈ 3.00) than in case of females (2.6). The L-W equations were log W = - 4.5996 + 2.8391 log L for males and log W = - 4.0507 + 2.6073 log L for females. The results further inferred a strong length - length correlation (r = 0.728-0.988; p<0.05).